Caring and Health of Close Family Members of Frail Older Persons Recently Discharged from Acute Hospital Care: A Comparative Cross-Sectional Study - Christina Bökberg; Tove Lindhardt; Eva Björkman; Gerd Ahlström (MDPI AG, 2024)
Multimorbidity in older people is strongly linked to the need for acute hospital care, and caregiving activities usually become more complex after patients are discharged from hospital. This may negatively impact the health of close family members, although this has not been comprehensively investigated. This study aimed to explore the general and mental health of close family members caring for frail older (>65) persons recently discharged from acute hospital care, making assessments in terms of gender, relationship to the older person, and aspects of caring. A comparative cross-sectional study was conducted involving 360 close family members caring for frail older persons recently discharged from hospital. The statistical analyses included subgroup comparisons and associations to caring were examined. Half of the family members reported that their general and mental health was poor, with spouses reporting the poorest health. Female participants had significantly more severe anxiety, while males had significantly more severe depression. Providing care for more than six hours per week was associated with poor general health (OR 2.31) and depression (OR 2.59). Feelings of powerless were associated with poor general health (OR 2.63), anxiety (6.95), and depression (3.29). This knowledge may provide healthcare professionals with better tools in order to individualise support, preventing family members from exceeding their resources during these demanding periods.